A review of trauma-informed neuroscientific theory to unpack the early childhood education teacher’s pastoral role in South Africa - Corinne Meier (South African Journal of Childhood Education)
Background: This review explores the pastoral role of early childhood development (ECD) teachers through a trauma-informed lens, grounded in neuroscience. Traumatised learners experience neurobiological changes that hinder cognitive and physical functioning. The review highlights the importance of pastoral support in ECD because of learners’ increasing mental health needs. Teachers must be equipped with various strategies to support emotional development, and collaborate with school nurses, counsellors, and psychologists, especially those specialising in ECD, to foster learners’ well-being and growth.